Creating democratic education in neoliberal and neoconservative times (Praxis Educativa, 2014)
Can education change society? It is one of the main questions to be asked in neoliberal and neoconservative times in favor of a democratic education. Part of the task of the critical-academic activist is to make public the challenges to the conservative modernization, advocating anti-hegemonic practices by giving his or her own testimony or that of other colleagues, regarding the possibility of taking steps toward building a reconstituted public sphere within the spaces in which we live and work.
Keywords: democracy; democratic schools; struggles; power; dominance